Technical Considerations in Stoma Creation - Whitehead, Alia; Cataldo, Peter A. (Clinics in Colon and Rectal Surgery, 2017)
Creating an intestinal stoma is commonly the final aspect of an often emergent and complicated operation under difficult circumstances. While creation of a protruding, tension-free, and well-vascularized stoma is often straightforward, one must be prepared for challenging situations such as a thick abdominal wall and short, thickened mesentery. A successful stoma starts with attentive preoperative planning including site marking, thoughtful consideration of alternatives, and attention to technical detail. The tips provided in this article should facilitate the process of selecting the appropriate intestinal segment, identifying the correct stoma site, and creating a functional stoma even in the most challenging situations. Constructing a high-quality stoma will decrease complications and improve the patient's quality of life. Stoma creation is frequently the only component of an operation that the patient will have to live with for the remainder of his/her life.
Keywords: ileostomy; colostomy; surgery; stoma; surgical repair